Study of dielectric response of BaTiO3/PVA composites for energy storage applications. (2022) - Yadav, Anju; Yadav, Dinesh Kumar; Choudhary, B.L.; Jakhar, Narendra; Jain, S.K.; Tripathi, Balram
Highlights: BaTiO3/ Polyvinyl alcohol composites. Dielectric properties. Surface Morphology. Bonding structure. Capacitors are most commonly used electrical energy storage systems which are used in various devices such as inverters, surgical lasers, hybrid electrical vehicles, high power microwave, high power weapons, audio equipments and various peak power applications. Abstract: Polymer nanocomposites with enhanced dielectric properties are highly desired in the recent electronic and electrical systems to store more energy. In present study, we synthesized flexible nanocomposites using barium titante (BT) as filler and polyvinyl alcohol (PVA) as matrix. The solution casting method is used to prepare BT/PVA composites and the content of filler BT in the matrix PVA varied from 1 to 5 mwt%. The composite materials are characterized by X-ray diffraction (XRD), Fourier Transform Infra-Red Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM). In addition to these, dielectric properties are studied within the frequency range of 1 KHz to 3 MHz by Impedance Analyzer. XRD spectra of the composites show no obvious difference with respect to pristine BT. The maximum value of dielectric constant observed at frequency 1 KHz for the BT5% PVA95% composite. Enhancement in dielectric constant for all the composites reveales the good interaction between BT and PVA composites. Therefore, BT/PVA nanocomposites may be suitable material for energy storage applications.